Community Based Citizenship Education: An Ecological Initiative in the Jatiwangi Art Factory Community - Alfiansyah, Azis; Danial, Endang; Fitriasari, Susan (CIVICS: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2025)
This study aims to explore the role of the Jatiwangi Art Factory community in fostering citizens' ecological awareness through an approach rooted in local art and culture. Employing a qualitative approach and case study method, data were collected through in-depth interviews, participatory observation, and documentation. The findings reveal that the Jatiwangi Art Factory has successfully encouraged citizen participation in various environmental programs, notably through the Perhutana initiative a community driven project that establishes an 8-hectare collective forest, collaboratively managed by local residents. The Perhutana program implements a land parceling system in which residents purchase plots, each of which is designated for tree planting. This approach is designed to stimulate citizens’ active involvement in responding to ecological issues in both critical and creative ways. These community-based activities reflect a contextualized model of civic education grounded in real-life practices. The study recommends strengthening the role of local communities in civic education, particularly through artistic, cultural, and indigenous knowledge-based approaches that bridge ecological awareness with civic identity.